Evaluation Of Risk Factors For Dermal Infections with Staphylococcus au-reus and Methicillin Resistant Staphylococcus aureus Among Sheep In Diyala Governorate, Iraq - Fajer, Zainab Bressam; AL-Ezzy, Ali Ibrahim Ali; Al-Zuhairi, Ahmad H. (Diyala Journal for Veterinary Sciences, 2023)
Background: Staphylococcus aureus is one of the dominant pathogenic bacteria among skin infections in human and animals. Aims: To evaluate the risk factors of dermal infections with S.aureus and methi-cillin resistant S.aureusMRSA) ( Methods :standard microbiological procedures were used for isolation of S.aureus and MRSA Results : No correlation reported between breed and S. aureus infections among sheep. Significant correlation reported between breed and MRSA infections on sheep. No correlation was reported between flock size and S. aureus infections among sheep. No significant correlation reported in the middle of flock size and MRSA infections among sheep. No significant correlation reported amongst sea-son ,S. aureus and MRSA infections in sheep. No significant correlation reported between introducing new sheep to the flock, S. aureus and MRSA infections among sheep. probability for infection of wound with S. aureus was 0.831time. the risk estimate to get infection with S. aureus due to wounds was (1.133) time compared with (0.942) intact skin .The risk estimate to get infection with MRSA for sheep suffered from wounds was (0.689) time compared with (1.234) for infec-tion that reported among sheep with intact skin. The risk estimate to get infection with S. aureus due to abscess was (0.159) time compared with (1.647) for intact skin. The risk estimate to get infection with MRSA for sheep suffered from abscess was (0.780) time compared with (1.122) for intact skin. The risk estimate to get infection with S. aureus due to dermatitis was (0.865) time compared with (1.042) for healthy skin. risk estimate to get in-fection with MRSA for sheep suffered from dermatitis was (1.721) time compared with (0.880) for infection that for intact skin. The risk estimate to get infection with S. aureus due to abrasions was (17.448) time compared with (0.634) healthy skin. The risk estimate to get infection with MRSA for sheep suffered from abra-sions was (2.525) time compared with (0.883) for intact skin. Conclusions: Abrasions represent major risk factor for getting S.aureus and MRSA infection in sheep. The breed, flock size, season, wounds, abscess, dermatitis represent minor risk factor for getting S.aureus and MRSA infection in sheep